2013
DOI: 10.1111/trf.12274
|View full text |Cite
|
Sign up to set email alerts
|

Assessing transfusion competency in junior doctors: a retrospective cohort study

Abstract: Junior doctors are involved in sampling, prescribing, consenting, and documenting transfusion practice frequently enough to maintain competency. They are rarely involved in the collection, bedside checking, or administration of blood despite current curriculum requirements. There is scope to significantly improve both the training and the assessment of transfusion competency in doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 12 publications
(15 reference statements)
7
47
1
2
Order By: Relevance
“…Our results are consistent with previously published findings of poor transfusion medicine exam performance . As with any area of medical research, however, studies investigating attitudes and knowledge must utilize accurate and precise assessment tools.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with previously published findings of poor transfusion medicine exam performance . As with any area of medical research, however, studies investigating attitudes and knowledge must utilize accurate and precise assessment tools.…”
Section: Discussionsupporting
confidence: 91%
“…A transfusion medicine knowledge needs assessment is required to best understand and then address these educational deficits . While several studies have administered transfusion medicine assessment tools to physicians, the exams and surveys underwent minimal validation . In addition, generalizability was limited as the study populations were confined to either a single center or a region.…”
mentioning
confidence: 99%
“…A survey conducted in the United Kingdom 10 assessed knowledge about transfusion medicine of resident physicians using questionnaires, and noted that higher scores were achieved by physicians who received education about hematology during their graduate courses. Rebel et al, 18 in a study conducted in the United States, found that knowledge of anesthesiology residents related to transfusion medicine increased after they spent a period in a hematology service.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted in countries such as the United States, United Kingdom, Tunisia, Canada and Iran to assess the degree of knowledge about transfusion medicine of newly graduated doctors; all studies reported lower than expected results 9, 10, 11, 12. In a poll conducted in 86 medical schools in the United States, most had less than three hours in the curricular grid dedicated to transfusion medicine 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It can however be noted that prescribing a blood transfusion is a process which remains too easy, is rarely discussed and often left to the inexperienced medical officer. 19 A common lack of documentation and/or consent accentuates the lack of scrutiny applied to the process of transfusion. The transfusion event is poorly monitored, is often inappropriate, unjustified and, due to various different funding models, sometimes comes at no cost for the health care provider (i.e.…”
mentioning
confidence: 99%